Performance Evaluation of Chemically Modified Rice Husk as an Adsorbent for the Treatment of Oil Seed Industrial Effluent - Dandajeh, Aliyu Adamu; Ahmad, Zaharadden; Ishaq, Aliyu; Abdullahi, Nura Idris (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2023)
The generation of oilseed wastewater is a matter of worry due to the presence of impurities that could have effects on ecosystems and human health. This study explores the potential use of rice husk chemically modified with 1M NaOH as an adsorbent to treat wastewater from Sunseed Nigeria Limited in Zaria, Nigeria. The adsorbent was characterized employing Fourier transform infrared spectroscopy (FTIR), which revealed the presence of carboxylic acid, alkanes, alkynes, and amide. Correspondingly, batch adsorption tests were conducted for a fixed period of 1 hour by using dosages of 2, 4, 8, 16, and 20 g. The findings indicated that the turbidity, BOD, and COD had the highest percentage of removal at dosages of 2 g, 20 g, and 2 g, respectively, with removal percentages of 81.48 %, 81.3 %, and 85 %. Also, lead and cadmium had removal percentages of 17.5% and 87.6%, respectively, at a dosage of 20 g. Furthermore, the Langmuir isotherm offered a greater fit for turbidity and total solids, with R2 values of 0.5355 and 0.8870, respectively, with the resultant absorption capacities of 0.0074 mg/g and 0.0249 mg/g. Similarly, the Freundlich isotherm described the BOD and COD well, with R2 of 0.6097 and 0.9678, respectively, and relative adsorption capacities of 1.3104 mg/g and 4.808*106 mg/g. Therefore, it can be concluded that the rice husk adsorbent has demonstrated effectiveness in removing certain physicochemical pollutants from oilseed industrial wastewater.